Gestational and Postpartum Weight Change Patterns in Mothers with Eating Disorders - ZERWAS, Stephanie C. (2014)
BACKGROUND: Although pregnancy can be associated with adaptive changes in weight and eating behavior for women with eating disorders, less is known about whether these changes are maintained in the postpartum period. We used a longitudinal design to examine gestational and postpartum weight trajectories in mothers with and without eating disorders in the Norwegian Mother and Child Cohort Study (MoBa) conducted by the Norwegian Institute of Public Health. METHODS: Fifty-six women reported anorexia nervosa (AN), 636 bulimia nervosa (BN), 3,327 binge eating disorder (BED), and 69 EDNOS purging type (EDNOS-P). The referent group included 61,233 mothers with no eating disorder. We used a mixed effects model to predict weight change over time by eating disorder subtype. RESULTS: Mothers with AN, BN, BED and EDNOS had greater increases in BMI during pregnancy and greater decreases in BMI over the first six months postpartum. Women with AN shifted from the underweight BMI range before pregnancy to the normal weight range at 36 months postpartum CONCLUSIONS: Patterns of maternal weight gain and retention during the perinatal period vary across eating disorder subtype and warrant clinical attention.